Business Networking Shaping Enterprise Relationships on the Internet - Österle, Hubert; Fleisch, Elgar; Alt, Rainer (Springer Berlin Heidelberg, 2000)
Electronic commerce, supply chain management, customer relationship management, and other forms of Business Networking will fundamentally change the way business will be conducted in the information age. We will see close collaboration between processes of different enterprises, and above all, new enterprises and new processes. Business Networking offers exceptional opportunities for innovators and harbors fundamental risks for slowpokes. This book proposes a process-oriented model for Business Networking and the concept of networkability to develop realistic strategies for managing enterprise relationships in the Internet economy. It formulates key success factors and management guidelines which were developed in close cooperation between research and practice